2015
DOI: 10.1016/j.jconhyd.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the antibiotic sulfadiazine in natural soils: Experimental and numerical investigations

Abstract: Based on small-scale laboratory and field-scale lysimeter experiments, the sorption and biodegradation of sulfonamide sulfadiazine (SDZ) were investigated in unsaturated sandy and silty-clay soils. Sorption and biodegradation were low in the laboratory, while the highest leaching rates were observed when SDZ was mixed with manure. The leaching rate decreased when SDZ was mixed with pure water, and was smallest with the highest SDZ concentrations. In the laboratory, three transformation products (TPs) developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Similarly, in Microbacterium lacus strain SDZm4, SDZ was transformed into 2-aminopyrimidine [ 20 ]. The metabolite 2-aminopyridine was observed not only by microbial process, but also detected during photolysis, electrochemical oxidation and sorption experiments by soils [ 1 , 18 , 31 , 32 ]. Furthermore, in strain 2APm3, 2-aminopyrimidine was metabolized into two by-products with one of that identified as 2-amino-4-hydroxypyrimidine [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Microbacterium lacus strain SDZm4, SDZ was transformed into 2-aminopyrimidine [ 20 ]. The metabolite 2-aminopyridine was observed not only by microbial process, but also detected during photolysis, electrochemical oxidation and sorption experiments by soils [ 1 , 18 , 31 , 32 ]. Furthermore, in strain 2APm3, 2-aminopyrimidine was metabolized into two by-products with one of that identified as 2-amino-4-hydroxypyrimidine [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The types of applications are very broad, ranging between agricultural problems evaluating different irrigation schemes, the effects of plants on the soil water balance and groundwater recharge (see Agricultural Applications section below), to many environmental applications simulating the transport of different solutes and particle‐like substances (see Transport of Particle‐Like Substances section) as well as evaluating the effects of land use and environmental changes. While many early applications focused mostly on subsurface flow processes, the relatively general formulation of the transport and reaction terms in the HYDRUS models makes it possible to simulate the fate and transport of many different solutes including nonadsorbing tracers, radionuclides (e.g., Pontedeiro et al, 2010; Matisoff et al, 2011; Merk, 2012; Xie et al, 2013), mineral N species (e.g., Li et al, 2015), pesticides (Pot et al, 2005; Dousset et al, 2007; Köhne et al, 2009b), chlorinated aliphatic hydrocarbons (e.g., Kasaraneni et al, 2014; Ngo et al, 2014), hormones (e.g., Casey et al, 2005; Arnon et al, 2008; Chen et al, 2013), antibiotics (e.g., Wehrhan et al, 2007; Unold et al, 2009; Chu et al, 2013; Engelhardt et al, 2015), explosives and propellants (e.g., Dontsova et al, 2006, 2009; Alavi et al, 2011), as well as many particle‐like substances such as viruses, colloids, bacteria, nanoparticles, and carbon nanotubes (see Transport of Particle‐Like Substances section).…”
Section: Selected Hydrus Applicationsmentioning
confidence: 99%
“…Agricultural applications of the HYDRUS modules often involve evaluations of various irrigation schemes (e.g., Cote et al, 2003; Ben‐Gal et al, 2004; Gärdenäs et al, 2005; Dabach et al, 2013), studies of root water uptake and groundwater recharge (e.g., Turkeltaub et al, 2014; Neto et al, 2016), and the transport of agricultural contaminants (Wehrhan et al, 2007; Unold et al, 2009; Engelhardt et al, 2015). For example, Gärdenäs et al (2005) used HYDRUS (2D/3D) to evaluate water and N leaching scenarios for three different microirrigation systems (surface and subsurface drip and sprinkler irrigation) and five different fertigation strategies.…”
Section: Selected Hydrus Applicationsmentioning
confidence: 99%
“…Several numerical models have been used for the prediction of inorganic and organic pollutants transport at laboratory scale, in real sites and for hypothetical pollution cases (Engelhardt et al, 2015;Jacques et al, 2008;Jellali et al, 2010;K€ ohne et al, 2009;Suarez et al, 2007). They demonstrated that the rates of pollutants migration depend on a wide range of physical and chemical porous media characteristics such as permeability, porosity, dispersivity, interconnectivity of macropores, mineralogy and organic constitution (Jacques et al, 2008;K€ ohne et al, 2009).…”
Section: Introductionmentioning
confidence: 99%